A business venture providing consultative services to organisations to optimise their internet marketing - Sacks, Ryan Alan (My University, 2017)
This business case describes the external and internal considerations required to establish a consulting business within the internet advertising market. Through an analysis of recent studies and literature, it explains how the marketing and entertainment industry is shifting heavily, and quickly, to the digital arena; specifically in the case of marketers, to internet advertising. It explains the global and domestic factors for the rapid growth of this market, and why it is an attractive market to enter. Furthermore, it explains what megatrends appear in the industry, and how to utilise these to create a competitive advantage, being: automation; data-centric organisations and decision-making; greater understanding of a business’ consumer, and how to market to them more effectively; and the utilisation of mobile and multi-platform, customised experiences. Through these investigations, and a consideration of various management theories, the business case explains how a sustainable, profitable, and growing business can be formed in this industry.
MBA
Keywords: Internet marketing. Marketing -- South Africa.